Staphylococcal toxic shock syndrome in a child. Case report - G.S. Karpovich; I.V. Kuimova; E.I. Krasnova; D.S. Maramygin; A.Yu. Enikeev (LCC «Medicine-Inform», 2021)
G.S. Karpovich1,2, I.V. Kuimova1, E.I. Krasnova1, D.S. Maramygin2, A.Yu. Enikeev2 1Novosibirsk State Medical University, Novosibirsk, Russian Federation 2Children's City Clinical Hospital No. 3, Novosibirsk, Russian Federation Toxic shock syndrome (TSS) is a complex of symptoms that includes fever, exanthem, multiple organ dysfunction syndrome, and hypotension. The most common causative agents are S. aureus and group A Streptococcus. TSS is characterized by severe course and high mortality in the lack of specific complex treatment. This article addresses a case report of staphylococcal TSS in a 5-year-old girl. The primary focus of infection (infected right leg wound) and breakthrough factors (the lack of adequate wound care) resulted in the dissemination of causative agent and TSS development. Despite disease severity, early complex etiological (antibiotics) and pathogenically-oriented (infusions, corticosteroids) treatment improved the patient's condition and promoted recovery. This case report illustrating the classic presentations of staphylococcal TSS in children is helpful for pediatricians in terms of awareness of this pathological condition. Keywords: infectious diseases, staphylococcus aureus, toxic shock syndrome, cytokine storm, multiple organ failure syndrome, pediatrics. For citation: Karpovich G.S., Kuimova I.V., Krasnova E.I. et al. Staphylococcal toxic shock syndrome in a child. Case report. Russian Journal of Woman and Child Health. 2021;4(3):302-307 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-302-307.